Increased incidence of neurogenic bladder after radical hysterectomy for cervical cancer: A nationwide population-based cohort study. Issue 10 (20th August 2021) - Chou, Meng-Han; Meng, En; Wu, Sheng-Tang; Cha, Tai-Lung; Sun, Guang-Huan; Yu, Dah-Shyong; Chung, Chi-Hsiang; Chien, Wu-Chien
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The effect of radical hysterectomy for patients with cervical cancer on voiding function remains controversial. The purpose of this study was to examine the association between radical hysterectomy for patients with cervical cancer and the odds of developing neurogenic bladder by using data from the National Health Insurance Research Database (NHIRD) in Taiwan. Methods: We identified 17 936 patients who underwent radical hysterectomy for cervical cancer between 2000 and 2013 among inpatients registered in the Longitudinal Health Insurance Database in Taiwan. Of the patients, those diagnosed as having cervical cancer without radical hysterectomy were selected and compared as a matched control group. Patients diagnosed as having cervical cancer before the index date, those with neurogenic bladder dysfunction before tracking, and those aged <20 years were excluded. The hazard ratios (HRs) of neurogenic bladder and other variants of interest were further calculated using a multivariate Cox regression analysis. The cutoff p value of <0.05 was regarded as statistically significant. Results: The adjusted HR (aHR) of subsequent neurogenic bladder was higher in the hysterectomy group (aHR = 1.205; 95% CI, 1.086-1.440; p = 0.029) than in the control group during the follow-up period. As to the age subgroups, the patients aged 20 to 44 years (aHR = 3.321, p = 0.001) had a significantly increased risk of developing neurogenic bladder after radical hysterectomy as compared with those aged 45 to 64 years (aHR = 1.193, p = 0.012). Conclusion: Patients with cervical cancer undergoing radical hysterectomy have an increased risk of neurogenic bladder, which may result from nerve denervation caused by the operation. These patients should be informed of the potential risk of voiding dysfunction during discussion of the subsequent management for cervical cancer.